Studi Literatur Review: Pengaruh Pembayaran Digital terhadap Perilaku Konsumtif - Bilqis Agustina Windiary (LPPM Universitas Putera Batam, 2026)
The development of financial technology has encouraged the increasing use of digital payments in various community transaction activities. The convenience, speed, and promotional programs offered through digital payment services have the potential to influence consumer spending behavior, particularly among younger generations. This study aims to analyze the effect of digital payments on consumptive behavior based on findings from previous studies. The research employed a qualitative literature review approach by collecting and analyzing relevant scientific literature, including journals, articles, books, and research reports published between 2021 and 2025. Data were analyzed using content analysis to identify concepts, empirical findings, and patterns of relationships between digital payments and consumptive behavior. The results indicate that digital payments positively contribute to consumptive behavior through transaction convenience, reduced psychological barriers to spending, and various promotional incentives such as cashback and discounts. Furthermore, the use of digital payments is associated with an increase in impulsive buying behavior. However, financial literacy and self-control have been found to mitigate the tendency toward excessive consumption resulting from digital payment usage. Therefore, improving financial literacy and awareness in managing personal finances is essential to promote more responsible and sustainable use of digital payment technologies.